Kegiatan Pengabdian dengan Edukasi dan Skrining Kolesterol dalam Rangka Pencegahan Penyakit Arteri Perifer pada Komunitas Dewasa di Kelurahan Krendang, Jakarta Barat - Alya Dwiana; Alexander Halim Santoso; Felix Felix; Edwin Destra; Fransisca Iriani Rosmala Dewi (jurnal ABDIMAS Indonesia, 2025)
Cholesterol is a type of fat naturally found in the body and plays a vital role in biological functions such as cell membrane formation and hormone production. However, elevated cholesterol levels can lead to plaque buildup in arterial walls, which is a major risk factor for peripheral artery disease. This condition is characterized by the narrowing of arteries that impedes blood flow, particularly to the extremities. A cholesterol screening program is conducted to detect elevated cholesterol levels early and to provide education about healthy lifestyle habits to adults. This program employs the Plan-Do-Check-Act (PDCA) approach, which includes planning, implementing education and screenings, evaluating effectiveness, and taking follow-up actions based on the results. The total cholesterol screenings revealed an average level of 181.81 with a standard deviation (SD) of 34.18. While this average is within the normal range, it approaches the upper limit, warranting caution to prevent further increases that could affect cardiovascular health in the future. Regular cholesterol screening can help minimize the risk of peripheral artery disease, thereby maintaining the quality of life for adults.